Current approaches to minimize the late blowing defect of cheese - Raquel Velasco; María Concepción Cabeza; Juan Antonio Ordóñez (Cogent Food & Agriculture)
The late blowing defect (LBD) is an issue in semi-hard and hard cheeses, as once the phenomenon occurs, it is impossible to amend and affects large production volumes. Therefore, it is a matter of major economic importance for cheese processors resulting in significant losses. This defect is characterized by the cracks formation and unpleasant flavors due to butyric fermentation. Several Clostridium spp. have been characterized as responsible bacteria, but C. tyrobutyricum is the microorganism most commonly isolated from affected cheeses. This is because it is more salt-tolerant than other species and it can grow suitability at typical ripening temperatures used in cheesemaking. Several attempts have been made to establish the minimal spore number required to cause LBD. Still, it is a complicated task because it depends on the microbial strain, cheese, and the method used for quantifying the bacterial load. Several different studies have been conducted to prevent the occurrence of cheese LBD. Some are directed to minimize the contamination of milk in the farm, others are aimed to remove the spores through physical methods and a third strategy consists of implementing sporestatic or sporicidal procedures. In this work, these approaches are discussed.